Evaluating hourly rainfall characteristics over the U.S. Great Plains in dynamically downscaled climate model simulations using NASA‐Unified WRF. Issue 14 (21st July 2017) - Lee, Huikyo; Waliser, Duane E.; Ferraro, Robert; Iguchi, Takamichi; Peters‐Lidard, Christa D.; Tian, Baijun; Loikith, Paul C.; Wright, Daniel B.
Abstract: Accurate simulation of extreme precipitation events remains a challenge in climate models. This study utilizes hourly precipitation data from ground stations and satellite instruments to evaluate rainfall characteristics simulated by the NASA‐Unified Weather Research and Forecasting (NU‐WRF) regional climate model at horizontal resolutions of 4, 12, and 24 km over the Great Plains of the United States. We also examined the sensitivity of the simulated precipitation to different spectral nudging approaches and the cumulus parameterizations. The rainfall characteristics in the observations and simulations were defined as an hourly diurnal cycle of precipitation and a joint probability distribution function (JPDF) between duration and peak intensity of precipitation events over the Great Plains in summer. We calculated a JPDF for each data set and the overlapping area between observed and simulated JPDFs to measure the similarity between the two JPDFs. Comparison of the diurnal precipitation cycles between observations and simulations does not reveal the added value of high‐resolution simulations. However, the performance of NU‐WRF simulations measured by the JPDF metric strongly depends on horizontal resolution. The simulation with the highest resolution of 4 km shows the best agreement with the observations in simulating duration and intensity of wet spells. Spectral nudging does not affect the JPDF significantly. The effect of cumulus parameterizations on the JPDFs is considerable but smaller than that of horizontal resolution. The simulations with lower resolutions of 12 and 24 km show reasonable agreement but only with the high‐resolution observational data that are aggregated into coarse resolution and spatially averaged. Key Points: NASA‐Unified WRF simulations were performed at three different horizontal resolutions (4, 12, and 24 km) over the contiguous United States The added value of high‐resolution simulations is realistic rainfall characteristics in the Great Plains during summer Without temporal overlap for the entire period with observations, the added value of high‐resolution simulations can be demonstrated